Posterior Uveitis Associated with Large Vessel Giant Cell Arteritis. (17th November 2022) - Nguyen, Nam V.; Karkhur, Samendra; Yuksel, Murat; Hassan, Muhammed; Halim, Muhammad Sohail; Nguyen, Quan Dong; Hasanreisoglu, Murat
ABSTRACT: Purpose: To report a case of acute unilateral posterior uveitis as a rare manifestation of giant cell arteritis (GCA). Observation: A 62-year-old male presented to the clinic for evaluation of decreased vision in the right eye (OD). BCVA in OD was 20/60, and fundus examination revealed 3+ vitreous cells along with several inflammatory precipitates located in posterior vitreous and on surface of retina. Although TAB was inconclusive for GCA, the clinical diagnosis of GCA was made according to the GCA diagnostic criteria. This diagnosis was further supported by 18 FDG-PET scan. The patient was started on corticosteroids, and the symptoms improved significantly after first week of treatment. At follow-up visit one month and half later, BCVA improved to 20/40 in the right eye. Conclusion: Although GCA is rarely present with uveitis, in case of unilateral posterior uveitis in elderly patient, it should be considered in the differential diagnosis.